PENGETAHUAN, SIKAP, DAN PRAKTEK GIZI IBU PESERTA POSYANDU - Ali Khomsan; Faisal Anwar; Eddy Setyo Mudjajanto (Jurnal Gizi dan Pangan, 2009)
Nutritional knowledge and attitude of mothers are required to improve children feeding patterns so that adequate nutrition for the children is reached, and in this way they can grow and develop well. The objectives of this action research were: (1) to assess mother nutritional knowledge, and (2) to evaluate the effects of nutrition education to the nutritional knowledge, attitude and practice (KAP) of mother. The research was carried out in two sub-districts of Bogor: Sub-District of Ciomas and Sub-District of Darmaga.  This research started with a preliminary study as the first step and experimental design as the second step.  As many as 16 posyandu  that met research requirements were obtained.  A total number of 240 mothers had been divided into kontrol and intervention groups. Collected data included the data of posyandu, household, children and mothers. Baseline data were collected during the pre-study, while end-line data were collected after conducting intervention (experiment). An experiment was made to determine the effect of nutrition education and home gardening on respond variables: mother’s nutritional knowledge, attitude, and practice. The experiment had been conducted for five months in the form of providing nutrition education once in two weeks and implementing home gardening.  Based on the General Linear Model (GLM) analysis, the intervention in the forms of nutrition education as well as home gardening programs which were carried for five months had a significant effect on the response variables (nutritional knowledge, attitude and practices among mothers.